Incomplete hetero-structure molecular layer enhancing room-temperature spin-photovoltaic performances. (April 2023) - Qin, Yang; Gu, Xianrong; Zhang, Yixiao; Hu, Shunhua; Guo, Ankang; Zhang, Rui; Meng, Ke; Yang, Tingting; Zhang, Cheng; Lu, Shuhang; Yang, Xueli; Guo, Lidan; et al.
Abstract: Molecular spin-photovoltaic device (MSP) has creatively integrated photovoltaic and spintronic functionalities, where output signal can be modulated even reaching fully spin polarized at room temperature by photo-generated voltage ( V ph ) as never before. Hence, to enhance V ph on a premise of effective spin transport is pivotal for improving MSP performance since it determines the capability for modulating spin signal. However, such capability for V ph to modulate spin signal is severely limited to the weak driving force of spin-photovoltaic interaction caused by single-component configuration of current MSP, and in this case, it can hardly be improved since MSP birth. Herein, an incomplete hetero-structure active layer is firstly employed to construct a novel-designed MSP, and a more efficient working mechanism has therefore been triggered and endows MSP with greater potential in the future. In such an MSP, the V ph has been enhanced by 15 times than in traditional single-component MSP at room temperature, which is far better than any previous reports. Moreover, desired properties of molecules for constructing ideal incomplete hetero-structure configuration and further optimizing above mechanism have been sketched theoritically, which will open a brand-new research chapter in both academic and practical aspects. Graphical Abstract: ga1 Highlights: Spin-photovoltaic device represents a frontier direction in molecular spintronics. Spin-photovoltaic effect can hardly be enhanced due to current device structure. Novel incomplete hetero-structure spin-photovoltaic device is firstly established. Incomplete hetero structure triggers a more efficient spin-photovoltaic mechanism. Spin-photovoltaic effect is enhanced up to 15 times, a record at room temperature.